PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, KOMITMEN ORGANISASI TERHADAP KINERJA AUDITOR - Santika Putra, Kadek Agus; Latrini, Made Yenni (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of intellectual, emotional intelligence, spiritual intelligence, and organizational commitment on performance auditor in public accounting firm in Bali. Sampling technique used in this research is the method of sample saturated with a sample obtained 80 samples. Data collection methods used in this study was a questionnaire, which is distributed questionnaires to the auditor in public accounting firm in Bali. The data analysis technique used to test the hypothesis in this study is Multiple Linear Regression Analysis. The results of this study suggest that intelligence, emotional intelligence, spiritual intelligence and organizational commitment positively affects the performance of auditors. This shows that the increasing intellectual, emotional intelligence, spiritual intelligence and organizational commitment, the auditor's performance is increasing as well
Keywords: Performance Auditor, Intellectual Intelligence, Emotional Intelligence, Intelligence of the spiritual, Organizational Commitment